Uganda : Report on the Prices Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda about finalizing the rebased producer price index (PPI) and developing export and import price indices (XMPI). It is proposed that the new PPI and the XMPI be compiled using a modified and enhanced version of the current PPI Excel-based processing system. Considerable time was spent with the XMPI team explaining the required functionality, and a partial compilation of the import price index was undertaken using Excel spreadsheets. For the PPI, an index structure and weighting pattern have also been derived based on the final 2009-10 supply and use tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet